FUNGSI PEMERINTAH DALAM MEMBERIKAN PELAYANAN ADMINISTRASI KEPENDUDUKAN BERDASARKAN PRINSIP GOOD GOVERNANCE (STUDI KELURAHAN SUMBER KECAMATAN BANJARSARI SURAKARTA) - Wilona, Mariska Zena; Riwanto, Agus; Madalina, Maria (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2017)
This legal research examines whether the implementation of public services, especially in the case of population administration in the Surakarta source village is in accordance with Good Governance. The 1945 Constitution mandates state to meet the basic needs of every citizen for the sake of his welfare, so that the effectiveness of a system of government is determined by the good of the public service. Every citizen is entitled to services and is entitled to the fulfillment of basic needs and the promotion of decent living with the mandate of the 1945 Constitution. In connection with the ministry, there are two terms that need to be known, namely serving and service. The sense of serving is “helping to prepare (take care of) what one needs”. While the sense of service is “business serving the needs of others”. Problem formulation of this thesis is whether in the Service Administration provided by the Village Resources is in accordance with the principles of Good Governance and whether the service administration administration they provide is ideal.